1994
DOI: 10.1128/mcb.14.7.4825
|View full text |Cite
|
Sign up to set email alerts
|

A pathway for cell wall anchorage of Saccharomyces cerevisiae alpha-agglutinin.

Abstract: Saccharomyces cerevisiae ot-agglutinin is a cell wall-anchored adhesion glycoprotein. The previously identified 140-kDa form, which contains a glycosyl-phosphatidylinositol (GPI) anchor (D. Wojciechowicz, C.-F. Lu, J. Kurjan, and P. N. Lipke, Mol. Cell. Biol. 13:2554-2563, 1993, and additional forms of 80, 150, 250 to 300, and >300 kDa had the properties of intermediates in a transport and cell wall anchorage pathway. N glycosylation and additional modifications resulted in successive increases in size during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
149
0
2

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(158 citation statements)
references
References 54 publications
7
149
0
2
Order By: Relevance
“…First, we examined the DIG association of ␣-agglutinin, which exhibits a dramatic change in size because of extensive glycosylation in the ER and the Golgi (28). After induction of its synthesis by mixing cells of both mating types, both the ER (80 and 140 kDa) and the plasma membrane forms (Ͼ250 kDa) were found in the DIG fraction (not shown).…”
Section: Dig Association Takes Place At the Level Of The Ermentioning
confidence: 99%
“…First, we examined the DIG association of ␣-agglutinin, which exhibits a dramatic change in size because of extensive glycosylation in the ER and the Golgi (28). After induction of its synthesis by mixing cells of both mating types, both the ER (80 and 140 kDa) and the plasma membrane forms (Ͼ250 kDa) were found in the DIG fraction (not shown).…”
Section: Dig Association Takes Place At the Level Of The Ermentioning
confidence: 99%
“…These proteins are all rich in serine/threonine and contain a glycosylphosphatidylinositol (GPI) attachment signal (Lu et al, 1995;Van der Vaart et al, 1995). It is believed that the 1,6-p-glucan side chain is linked to the protein through the GPI-anchor (Kapteyn et al, 1994;Lu et al, 1994;Kapteyn et al, 1996). Lu et al (1995) have shown that 1,6-p-glucan becomes attached to a-agglutinin upon incorporation into the cell wall.…”
Section: Introductionmentioning
confidence: 99%
“…§ a-Agglutinin (Agalp) is composed of a single polypeptide that contains two functional regions, a cell surface anchorage region and a ligand-binding or adhesion region. The C-terminal half consists of a highly glycosylated, serine/threonine-rich domain followed by a hydrophobic signal for attachment of a glycosyl phosphatidylinositol (GPI) anchor, which mediates anchorage to the cell wall (Wojciechowicz et al, 1993;Lu et al, 1994Lu et al, , 1995. The N-terminal half of a-agglutinin is active in binding to its ligand (Wojciechowicz et al, 1993); this adhesion region contains a domain (called domain III; Figure 1A) that shows similarity to immunoglobulin (Ig) fold domains (Williams and Barclay, 1988).…”
Section: Introductionmentioning
confidence: 99%